Sustainable Development of Shophouses in Hanoi's New Urban Areas towards Smart City Criteria - Nguyen, Hoang Tung (International Journal of Sustainable Construction Engineering and Technology, 2022)
Developing sustainably and becoming a smart city is a long-term and strategic orientation of Hanoi. Shophouses, which are multi-function urban houses, converge many factors that strongly support sustainable development of Hanoi such as providing high quality residential areas; helping create diverse and lively communities, touristic attractiveness, conditions for sustainable management of resources and energy efficiency, etc. With various economic activities, shophouses also have lots of potentials in development towards smart cities such as lively and safe pedestrian zones, abilities to transform, local and supra-local accessibility, reasonable density of construction and population, etc. Analyses and studies show that in order to sustainably develop shophouses in new urban areas of Hanoi, it is necessary to solve existing problems of the constitutional system, the socio-economy, living space quality and management of the shophouse neighbourhoods. Notably, the criteria for smart city development are closely related to the above-mentioned issues. Proposals have been made based on studying the core values of shophouses and historical research of architecture in the Southeast Asia region. In addition to the proposals on improving the constitution and urban design solutions, the proposals on digitization of shophouse projects are submitted for the sustainable development towards smart cities development